2015
DOI: 10.1002/2015jb011877
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter maturation in the contact aureole of an igneous sill as a tracer of hydrothermal convection

Abstract: The intrusion of magmas can induce hydrothermal convection which in turn enhances the transport of heat and solutes. We use a heat convection model to interpret the temperature evolution documented by organic matter maturation, as recorded by the vitrinite reflectance Rr, in a contact aureole of a 15 m thick basaltic sill in the Deep Sea Drilling Project (DSDP) 41–368 hole near Cape Verde Rise, eastern Atlantic. Here there is a pronounced asymmetry of variations of Rr with distance above and below the sill tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Heat transfer in the country rock can be enhanced by hydrothermal convection. Wang and Manga (2015) show that hydrothermal convection induces complexlyshaped thermal aureoles. Diffusivities decrease with temperatures (Robertson, 1988;Whittington et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Heat transfer in the country rock can be enhanced by hydrothermal convection. Wang and Manga (2015) show that hydrothermal convection induces complexlyshaped thermal aureoles. Diffusivities decrease with temperatures (Robertson, 1988;Whittington et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Water convecting in the vicinity of sill intrusions could significantly modify the temperature and maturity effect of intrusions. Convection of hot fluids from the magma, the host-rock water, and decomposition products of kerogen is dependent on the permeability of porous host rocks or hydrofracturing in less porous host rocks (cf., [60,61,[82][83][84]. How the fluids from magma and host rock affect the fluid pressure and flow is determined by the host-rock porosity, permeability, and amount of fluids present [85].…”
Section: Temperature Modelmentioning
confidence: 99%
“…How the fluids from magma and host rock affect the fluid pressure and flow is determined by the host-rock porosity, permeability, and amount of fluids present [85]. Wang and Manga [83] showed that for rocks with low permeability (<10 mD) symmetrical contact aureoles are produced, implying that conduction is the favorable cooling method for sills and host rocks after emplacement. On the other hand, rocks of high permeability (>50 mD) show maturation asymmetry above the sill, implying occurrence of convection-influenced maturation [83].…”
Section: Temperature Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of lighter components, such as methane, may dissolve in the fluids or migrate as a gas phase during the formation of HTVCs (Svensen and Jamtveit, 2010;Wang and Manga, 2015). The volume of these carbon-bearing gases depends on the total amount of organic carbon in the host rock (Whitaker, 1986).…”
Section: Formation and Source Of Hydrothermal Vent Complexesmentioning
confidence: 99%